Evaluation of Vegetable Protein Sources on Nursery Pig Performance in a Commercial Environment - Rafe Q. Royall; Joel M DeRouchey; Mike D. Tokach; Jason C. Woodworth; Robert D. Goodband; Jordan T. Gebhardt; Keith D. Haydon (Kansas Agricultural Experiment Station Research Reports, 2021)
This experiment was conducted to determine the effect of vegetable protein sources on growth and economic performance of nursery pigs in a commercial research environment. A total of 2,592 pigs (L337 × 1050, PIC; initial BW of 11.8 ± 0.11 lb) were used in a 42-d study. Pens of pigs were blocked by BW and weaning date and allotted to 1 of 6 dietary treatments in a randomized complete block design with 27 pigs per pen and 16 replications per treatment across 2 rooms. Similar numbers of barrows and gilts were placed in each pen. There were six dietary treatments which included: 1) soybean meal control diet with no specialty vegetable protein source, and 5 diets containing either 2) soy protein concentrate 1; 3) soy protein concentrate 2; 4) enzymetreated soybean meal; 5) fermented soybean meal; and 6) high protein corn DDGS. Treatment diets were formulated in two dietary phases and fed at a rate of 5 lb/pig and 18 lb/pig, respectively, with a common phase 3 diet fed for the remainder of the study. During the experimental diet feeding period (d 0 to 21) or overall (d 0 to 42), there was no evidence of difference (P>0.05) for BW, ADG, ADFI, or F/G. Additionally, there was no evidence of significant difference (P>0.05) for total removals, removals, or mortality. For economic analysis, there was no evidence for significant difference (P>0.05) for any response criteria. In summary, no differences existed between soybean meal and the specialty vegetable protein sources used in this study.
Keywords: growth; nursery pig; specialty protein; soy protein concentrate